1998
DOI: 10.1007/s005860050115
|View full text |Cite
|
Sign up to set email alerts
|

A physiological approach to surgical treatment of progressive early idiopathic scoliosis

Abstract: IntroductionThe results of previous studies have shown that in girls with right convex thoracic adolescent idiopathic scoliosis (IS) there is significantly increased vascularity of the left breast as compared with the right one [10]. It has also been found that in deceased women with right convex thoracic IS, the mean length of the ribs corresponding to the apical and the two periapical vertebrae was greater on the concave than on the convex side [11]. These changes were ascribed to disturbed sympathetic funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 17 publications
1
10
0
1
Order By: Relevance
“…The modification of the spine curves is in agreement with the case of the 7 year old scoliotic patient reported by XIONG and SEVASTIK (1998). The concave rib shortening of three ribs (7th, 8th and 9th) resulted in a decrease in the Cobb angles, both in the frontal and lateral planes, respectively, from 46 ° to 21 °, and from 55 ° to 35 °, after 27 months.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The modification of the spine curves is in agreement with the case of the 7 year old scoliotic patient reported by XIONG and SEVASTIK (1998). The concave rib shortening of three ribs (7th, 8th and 9th) resulted in a decrease in the Cobb angles, both in the frontal and lateral planes, respectively, from 46 ° to 21 °, and from 55 ° to 35 °, after 27 months.…”
Section: Discussionsupporting
confidence: 87%
“…Animal studies have shown that rib resection, either shortening or lengthening, can induce (PIGGOTT, 1971;SEVASTIKOGLOU et al, 1978;SEVASTIK et al, 1993;DEGUCHI et al, 1995) and correct (SEVASTIK et al, 1990;DEGUCHI et al, 1996DEGUCHI et al, , 1997 scoliosis. XIONG and SEVASTIK (1998) reported the case of a young scoliotic patient who was treated by shortening of three ribs on the curve concavity and who has shown continuous improvement of the spinal curvature. A previous b iomechanical study using a finite element model of the trunk demonstrated that, although rib surgery produces only slight immediate geometrical changes, concave side rib shortening and convex side rib lengthening can induce load patterns on the end-plates that might act against scoliosis progression (GREALOU et al, 2002;CARRIER et al, 2004).…”
mentioning
confidence: 97%
“…19 There is a single case of a 7-year-old girl that had shortening of three ribs on the concavity of a scoliotic curve and 27 months postoperatively has a 54% reduction in the magnitude of her curve. 20 The use of growth tethering in clinical practice has yielded inconsistent results. In 1954, Smith et al described the stapling of vertebral bodies in three patients with congenital scoliosis.…”
Section: Discussionmentioning
confidence: 99%
“…Xiong and Sevastik reported a successful case of treatment by the shortening of three concave-side ribs in a 7-year-old girl with a right thoracolumbar scoliosis treated by a shortening of three concave ribs. 11 The patient's curve decreased from 46 degrees to 21 degrees over a period of 27 months. It is surprising that the finite element model predicted a more modest curve correction, while another case report described a 50% reduction in curvature within the same time frame.…”
Section: ■ Biological Growth Modulation Growth Modulation Secondary Tmentioning
confidence: 97%